60 years of Fapesp: A State policy for development - Zago, Marco A.; Felício, José R. Drugowich de (Estudos Avançados, 2022)
Fapesp is today the most solid research agency in Brazil. Strongly inspired by Positivism in its origins, it was forged over nearly eight decades. Its legal model influenced all other similar State foundations in the country, associating the constitutional guarantee of budgetary stability with an autonomous management that allocates 95% of its budget to research, in all areas of knowledge. In 60 years, the agency has accumulated successes in programs such as capacity building, competitive basic and applied research in bioenergy, agriculture, medicine, biodiversity, oceanography, astronomy, physics, mathematics, computing, social sciences, in addition to supporting innovation and cooperation between academia and businesses. Fapesp was the cradle of the internet, genomics and bioinformatics in Brazil, and has recently played a prominent role in the response of São Paulo’s society to the Covid-19 pandemic.